Phage therapy for severe bacterial infections: a narrative review. Issue 6 (6th October 2019) - Petrovic Fabijan, Aleksandra; Khalid, Ali; Maddocks, Susan; Ho, Josephine; Gilbey, Timothy; Sandaradura, Indy; Lin, Ruby CY; Ben Zakour, Nouri; Venturini, Carola; Bowring, Bethany; Iredell, Jonathan R
Summary: Bacteriophage (phage) therapy is re‐emerging a century after it began. Activity against antibiotic‐resistant pathogens and a lack of serious side effects make phage therapy an attractive treatment option in refractory bacterial infections. Phages are highly specific for their bacterial targets, but the relationship between in vitro activity and in vivo efficacy remains to be rigorously evaluated. Pharmacokinetic and pharmacodynamic principles of phage therapy are generally based on the classic predator–prey relationship, but numerous other factors contribute to phage clearance and optimal dosing strategies remain unclear. Combinations of fully characterised, exclusively lytic phages prepared under good manufacturing practice are limited in their availability. Safety has been demonstrated but randomised controlled trials are needed to evaluate efficacy.